Long Non-coding RNA ST8SIA6-AS1 Promotes Lung Adenocarcinoma Progression Through Sponging miR-125a-3p - Cao, Qifeng; Yang, Weiqin; Ji, Xili; Wang, Wei (Frontiers in Genetics, 2020)
Emerging evidence suggests that long non-coding RNA (LncRNA) plays a critical role in human disease progression. Recently, a novel lncRNA ST8SIA6-AS1 was shown as an important driver in various cancer types. Nevertheless, its contribution to lung adenocarcinoma (LUAD) remains undocumented. Herein, we found that ST8SIA6-AS1 was frequently overexpressed in LUAD cell lines, tissues and plasma. Depletion of ST8SIA6-AS1 significantly inhibited LUAD cell proliferation and invasion in vitro and tumor growth in vivo. In term of mechanism, ST8SIA6-AS1 was transcriptionally repressed by tumor suppressor p53, and ST8SIA6-AS1 mainly located in the cytoplasm and could abundantly sponge miR-125a-3p to increase NNMT expression, thereby facilitating LUAD malignant progression. Clinically, high ST8SIA6-AS1 was positively correlated with larger tumor size, lymph node metastasis and later TNM stage. Moreover, ST8SIA6-AS1 was identified as an excellent indicator for MM diagnosis and prognosis. Collectively, our data demonstrate that ST8SIA6-AS1 is a carcinogenic lncRNA in LUAD, targeting the axis of ST8SIA6-AS1/miR-125a-3p/NNMT may be a promising treatment for LUAD patients.